Association between Chronic Inflammation of Basal Plate and Decidua Existences with Placenta Accreta Spectrum - Yuktiana Kharisma; Meike Rachmawati; Abdul Hadi Hassan; Ismet Muchtar Nur; Hasrayati Agustina; Sri Suryanti (Global Medical & Health Communication (GMHC), 2022)
The placenta accreta spectrum (PAS) is an abnormal placenta condition with a high level of morbidity and mortality in both the mother and fetus. The PAS has a multifactorial etiology, one of which is a chronic inflammation of the basal plate (CIBP) and the decidual existences (DE). The study aims to analyze the association between CIBP and DE with PAS. It was an analytical observational with a cross-sectional study design on 50 placentae (25 PAS paraffin block, 25 standard placenta samples) from Dr. Hasan Sadikin General Hospital and other health centers that meet the inclusion and exclusion criteria. The data are taken from PAS patients from January 2015–December 2020. All samples will be stained with hematoxylin-eosin (HE), then undergo histopathological examination. The result of the studies analyzed statistically using Fisher's exact. CIBP in PAS was found in 21/25 cases, while in the normal placenta was found in 16/21 patients. The DE is positive in 15/25 cases of PAS, whereas the normal placenta was found in all cases. The association between CIBP and PAS is insignificant statistically (p=0.19), while the DE showed a significant relationship with PAS (p=0.00). The presence of the decidua is related to the regulation of trophoblastic invasion into the myometrium in PAS cases. CIBP can occur due to the reaction of decidua tissue to trophoblastic invasion or an infectious agent. The pathogenesis of PAS needs further understanding so that the appropriate therapy can be found for its prevention and management.